"It's like being on a roller coaster": the burden of caring for people with severe asthma. Issue 2 (12th April 2021) - Majellano, Eleanor C.; Clark, Vanessa L.; Foster, Juliet M.; Gibson, Peter G.; McDonald, Vanessa M.
Introduction: Family carers and significant others play a fundamental role in the well-being of people with severe asthma. This study aimed to investigate the challenges faced by family carers/significant others of people with severe asthma, to understand if there is an unmet need and to explore coping strategies. Methods: Carers of people with severe asthma were invited to participate in a face-to-face or telephone interview. Semi-structured interviews were conducted until reaching data saturation of themes. The 20 interviews were recorded and transcribed, and analysis of data followed an inductive thematic approach. Results: We report three overarching emergent themes: 1) "Caring role impacts", which centred around the negative and positive impacts of caring on carers' well-being; 2) "Unmet needs", which encapsulated the support needs participants desired and were categorised into unmet information, biopsychosocial needs and carers' involvement in decision-making; and 3) "Coping strategies", which were central to the range of tools and positive approaches in dealing with caring demands. Discussion: Caring for someone with severe asthma can be burdensome and may negatively affect the physical and psychosocial health of the carer. Various coping strategies are used to manage the demands of these caring roles. Carers of people with severe asthma expressed a need for informational, biopsychosocial and involvement in care decision-making support . Tailored support services that are sensitive to their needs may improve their quality of life and encourage healthcare providers to value and acknowledge the important contribution that carers make. Caring for someone with severe asthma can be burdensome, affecting the physical and psychosocial health of the supportive person negatively. Tailored support services may improve their quality of life. https://bit.ly/2KA9PWS